Kontribusi Implementasi Manajemen Berbasis Nilai-Nilai Kearifan Lokal Tri Hita Karana, Kepemimpinan, Budaya Organisasional dan Kepuasan Kerja Terhadap Kinerja Pegawai di Perumda Bhukti Praja Sewakadarma di Kota Denpasar - Ni Putu Dian Astriani; Anak Agung Gede Agung; Ni Luh Gede Erni Sulindawati (LP. Ma'arif Janggan Magetan, 2024)
This study aims to assess several aspects regarding the performance of State High School teachers in Denpasar City, namely: 1) the level of determination of transformational leadership on teachers' performance, 2) the level of determination of work ethic on teachers' performance, 3) the level of determination of organizational commitment on teachers' performance, 4) the level of determination of work motivation on teachers' performance, and 5) the combined determination of transformational leadership, work ethic, organizational commitment, and work motivation on the performance of State High School teachers in Denpasar City. The study employed an